MULTIOBJECTIVE FUZZY PORTFOLIO MODEL IN INDONESIAN SYARIAH STOCK MARKET - Hikayat, Chairil; Nabila, Luthfannisa Afif; Jana, Padrul (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2025)
The current global financial instability has attracted investors in Indonesia to the Sharia capital market, which promises bright opportunities. This study emphasizes the importance of using a fuzzy approach in managing multi-objective portfolios to deal with uncertainty in the Sharia stock market. This approach allows investors to manage their portfolios more effectively by considering various investment objectives simultaneously, such as maximizing profits and minimizing risks, which are very important amidst the ever-changing market dynamics. The method in this study is a fuzzy portfolio approach using the Treynor and Sharpe ratios in evaluating investment performance. Data is processed using fuzzy trapezoids, and portfolios are used to minimize risk without using short sales so that it remains balanced between potential profits and risks. The results of the analysis show an expected rate of return of 0.00091 and a risk level of 0.000421. When the allocation is set with a proportion of 93.8% for ANTM shares and 6.17% for KLBF, the strategy can provide a return of 0.091% with minimized risk. This creates an optimal balance between profit opportunities and risk management.